Effect of green banana pulp powder on microbiological quality of chevon nuggets during refrigerated storage - Shaikh F.R, Sultan; Devangare, A. A.; Raziuddin, Mohammad; Gaikwad, N. Z.; Suryawanshi, R. D.; Awandkar, S. P.; Kulkarni, R. C. (Journal of Meat Science, 2023)
Functional meat products are often created by reformulating meat and adding health promoting ingredients such as fibres, prebiotics, probiotics, polyunsaturated fatty acids and antioxidants. Present research was undertake to study the effect on incorporation of 4% green banana pulp powder on  physico-chemical, microbiological and sensory characteristics of chevon nuggets stored at refrigeration temperature (4±1˚C) in low density polyethylene (LDPE) pouches. During storage of product pH, Thiobarbituric acid value and tyrosine values increased significantly (p
Keywords: Chevon; Nuggets; Green banana powder; Physico-chemical; Microbiological and Sensory quality